EXPANDED CLAY CONCRETE AS A MATERIAL FOR MODERN AND RESTORATION CONSTRUCTION - Baranovych, Lyubov; Baranovych, Andrii (Theory and practice of design, 2025)
The article examines the features of using lightweight concrete and expanded clay concrete in construction, reconstruction, and restoration of buildings. The relevance of the research is determined by the rising cost of energy resources and the need to reduce energy consumption not only at the stage of material production but also during the operation of buildings. The historical experience of using lightweight concretes – from the Roman Empire to modern architectural objects – is analyzed. A classification of lightweight concretes by structure and function is presented, along with their physical and mechanical characteristics. Particular attention is paid to expanded clay and expanded clay concrete as environmentally friendly materials with high thermal insulation, sound insulation, and structural properties. Examples of their application in modern construction are considered, including individual residential houses, public buildings, historical monuments, and infrastructure facilities. It is shown that the use of expanded clay concrete contributes to reducing structural weight, shortening construction time, lowering energy consumption, and increasing the durability of buildings. Regulatory requirements for the thermal resistance of enclosing structures are summarized in accordance with Ukrainian DBN and European standards. The study highlights the prospects of applying lightweight concretes in the context of energy-efficient and sustainable construction. Purpose: to substantiate the feasibility of using lightweight concretes, in particular expanded clay concrete, in modern construction, reconstruction, and restoration of buildings; to analyze their physical, mechanical, and thermal insulation characteristics; and to determine their impact on energy efficiency, durability, and sustainability of buildings. Methodology. The research is based on the analysis of regulatory documents (DBN, DSTU), a review of scientific publications, and practical case studies of using expanded clay concrete in construction and reconstruction. A comparative method is applied to evaluate its characteristics relative to traditional materials, as well as generalization of application results in modern and historical buildings. Results. The analysis of scientific sources, regulatory framework, and practical examples demonstrated that expanded clay concrete has significant potential in modern construction, reconstruction, and restoration of buildings. The study confirmed that expanded clay concrete meets the requirements of current Ukrainian DSTU and DBN standards and can become one of the key materials in implementing energy-efficient and sustainable construction principles. Scientific novelty. The article systematizes the advantages of expanded clay concrete as an energy-efficient and eco-friendly material, summarizes regulatory requirements (DSTU, DBN) for its properties, and outlines prospects for its application in construction, reconstruction, and restoration, with emphasis on reducing structural weight and preserving historical authenticity. Practical relevance. The obtained results can be applied in the design and implementation of construction and restoration projects for selecting optimal structural solutions with expanded clay concrete, ensuring reduced foundation loads, improved thermal and acoustic insulation, as well as saving material and energy resources.